Architectured hybrid conductors: Aluminium with embedded copper helix. (February 2020) - Lapovok, R.; Popov, V.V.; Qi, Y.; Kosinova, A.; Berner, A.; Xu, C.; Rabkin, E.; Kulagin, R.; Ivanisenko, J.; Baretzky, B.; Prokof'eva, O.V.; Sapronov, A.N.; et al.
Abstract: This study is inspired by the potential of application-designed aluminium-copper conductors. This work combines recently discovered advantages of hybrids with one constituent having a helical architecture with the benefits provided by severe plastic deformation (SPD) methods. The hybrids are made by embedding copper helixes in melted aluminium and subjecting cast hybrid ingots to different SPD techniques. The electrical conductivity, microstructure features and strength of the produced samples are discussed in relation to effect of SPD and annealing on both constituents and an interface zone formed during the hybrids' production. It was shown that between all processing techniques the reciprocal extrusion (RE) has the great potential for production of lightweight conductors with high conductivity and enhanced strength. A new model describing the effective electrical conductivity of hybrid samples, consisting of an aluminium matrix with an embedded copper helix and intermetallic containing interface, is developed and justified by experimental data. The model is shown to be instrumental for analysis of the effect of the helix's parameters and interface width on effective conductivity of the hybrid samples and could be used for optimal design of hybrid conductors. Graphical abstract: Unlabelled Image Highlights: The new design for AlCu conductor with copper used as helical wire fully embedded in the aluminium matrix is suggested. Samples with helical reinforcement exhibit increased load-bearing capability and higher strain hardening during deformation. The SPD processing is important for strengthening of the hybrid due to grain refinement and dissolution of intermetallic. New analytical model predicting the electrical conductivity of hybrids and accounting for intermetallic layer is developed. The model depends on two parameters determined by copper volume fraction and the geometry of the helical constituent.